KOMUNIKASI ANTAR PRIBADI DALAM KELUARGA (Studi Fenomenologi Terhadap Perilaku Komunikasi Pasangan Suami Istri Yang Mengalami Ketimpangan Jumlah Pendapatan) - Aryadillah Aryadillah (Cakrawala - Jurnal Humaniora, 2018)
Today, family activity has a significant shift from agricultural production to consumption of goods and services. Many of the family entities that no longer produce their own foodstuffs through rice fields and farming; they go to shopping centers and traditional markets to meet their needs. This is also motivated by cultural changes and socio-economic conditions such as shifting the role of women as wives who are no longer merely struggling in the domestic household. This shift in views and cultural changes color the communication behavior between married couples, either directly or indirectly. The research method used in this research is qualitative research method. This is because the issues to be discussed are complex, holistic, dynamic, and full of meaning. From the results of this study, there are 4 couples who have interpersonal communication patterns that are different from the first type of friendship partner, independent couple, the three complicated pairs, the four independent and traditional combined pairs.